Factors Shaping Women’s Pre-abortion Communication with Members of Their Social Network - Chor, Julie (J Community Health, 2019)
We sought to understand women's pre-abortion conversations with members of their social network about their abortion decision. Semi-structured interviews were conducted with women presenting for first-trimester surgical abortion at a high volume, hospital-based abortion clinic. Women were asked their reasons for discussing or not discussing abortion and responses received after disclosing their abortion decision. Interviews were transcribed and computer-assisted content analysis was performed. Salient themes are presented. Thirty women who obtained an abortion were interviewed. All but three spoke to at least one member of their social network about their abortion decision making. However, women were very selective about whom they spoke to regarding this decision. Reasons not to discuss their abortion decision included: concerns about judgment, desiring to maintain privacy, and certainty about their decision. Reasons to discuss their abortion decision included: seeking information about the procedure, needing guidance about their decision, wanting support for their decision to proceed with abortion. While many were concerned about being judged, most women who spoke about their decision experienced a positive response. Though most women in this study had at least one person to turn to for assistance with abortion decision making, many participants avoided confiding in some or all members of their social network about their abortion decision due to concerns of judgment and stigma.